Management of the Investigation and Detection of Legionellosis Agent in the Environmental Samples during the Preparation and Holding of the XXII Winter Olympics and XI Paralympics in Sochi - E. B. Ezhlova; Yu. V. Demina; A. N. Kulichenko; S. A. Portenko; A. S. Gus’Kov; E. S. Pochtareva; I. V. Savel’Eva; A. S. Volynkina; V. N. Savel’Ev; M. E. Mikhailova; I. V. Kuznetsova; O. A. Bobenko; et al. (Проблемы особо опасных инфекций, 2015)
Provided are the data on the management and carrying out of the laboratory control over the hot-water supply systems of the sports venues and accommodation areas for the presence of Legionella pneumophila during the XXII Olympics and XI Paralympics in Sochi, 2014. Inspected have been 105 facilities. The samples from 37 of them showed positive. L. pneumophila DNA concentration varies between 2.19·102 and 3.92·107 genome equivalents (g.e.)/l. By means of bacteriological investigation detected have been legionella colonies in the water supply systems of 16 facilities, at one of the items - the loading is over 1·104 colony-forming units/l. Performed has been comparative analysis of the results obtained using PCR assay and bacteriological test. Based on the genotyping of 7 isolated strains serogroup 1 and 2 strains of 2-14 serogroups it is concluded that L. pneumophila strains circulating in the resort town Sochi are genetically heterogeneous.